Migration to Britain from South Asia, 1600s–1850s - Fisher, Michael Herbert (History compass, 2005)
Men and women from South Asia (what would become India, Pakistan, Bangladesh, Sri Lanka, and Nepal) have chosen to settle in the British Isles since the early seventeenth century. By the mid-nineteenth century, tens of thousands had arrived, some remaining permanently, more returning home. Their complex and often contested relationships with the native British population shifted with the onset and expansion of imperialism. Early settlers had experiences different from those of their successors during the high-colonial and post-colonial periods. This article considers the historiography about the diverse early South Asian settlers in Britain - the disparate sources available in several languages and how various historians and other commentators have represented these sources and these settlers both. Given the current political, cultural, and social tensions concerning Asians in multicultural Britain, we would do well to understand this early history in its contemporary terms as well as in our own.